Real-time artificial intelligence driven diagnostic that can be used to assess diets - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The development of an artificial-intelligence (AI) app for mobile devices began in 2020 with some initial pilot testing among adolescent girls in urban areas of Ghana and Vietnam., which will continue in 2021.